A Perspective on Monkeypox Related LGBT Phobia Among the General Public - Das, Rinila; Behera, Swati; Sumit, Kumar (National Journal of Community Medicine, 2023)
Due to an upsurge in imported cases in the Western Pacific Region, the World Health Organization has proclaimed monkeypox a Public Health Emergency of International Concern on July 23rd, 2022. The worldwide transmission of human monkeypox disease presents substantial healthcare concern. Similar to previous infectious disease outbreaks, conspiracy theories have also emerged in relation to the 2022 monkeypox outbreak, undermining health behaviors and amplifying the outbreak's impact. Fake news on social media worsens the monkeypox outbreak, silencing healthcare experts. The outbreak has stigmatized monkeypox, putting LGBTQI+ communities at increased risk. Unsurprisingly, the present outbreak is impacting a large number of homosexuals, bisexuals, and men who have sex with men, which may lead to increased discrimination and stigma towards this group, along with increased LGBT phobia among the general population. Such stigmatization lead to healthcare disengagement, increasing morbidity and mortality, significant physical, socio-economic, and psychological consequences for LGBTQ+ community. Monkeypox is manageable if transmission chains are broken, aided by accurate information to dispel outdated myths rooted in fear and sexual bias. A holistic, culturally-sensitive approach is vital to combat current monkeypox-related stigma, requiring government interventions and multi-stakeholder collaboration for a multidisciplinary strategy.